The Effect of Fiscal Decentralization on Economic Growth: Panel Data of 16 Provinces in Sumatra and Java Island - Vaya Natasya Putri; Ambya Ambya; Arif Darmawan (Lafadz Jaya Publisher, 2024)
This study aims to examine the effect of fiscal decentralization with initial growth as a control variable on economic growth in 16 provinces on the island of Sumatra and Java. The study used panel data from 2012 to 2022. This study used panel data regression analysis techniques. In this study, the model chosen was CEM with an Ordinary Least Squares (OLS) approach. The results of this study show that there is a significant influence of the level of fiscal decentralization and initial growth on per capita economic growth on the island of Sumatra and Java. Simultaneously, the degree of fiscal decentralization and initial growth affect per capita economic growth on the island of Sumatra.